Precipitated sdLDL: An easy method to estimate LDL particle size. Issue 7 (21st March 2020) - Fernández‐Cidón, Bárbara; Candás‐Estébanez, Beatriz; Ribalta, Josep; Rock, Edmond; Guardiola‐Guionnet, Montserrat; Amigó, Núria; Padró‐Miquel, Ariadna; Alía‐Ramos, Pedro; Pintó‐Sala, Xavier
Abstract: Background: LDL‐C lowering is the main measure in cardiovascular disease prevention but a residual risk of ischemic events still remains. Alterations of lipoproteins, specially, increase in small dense LDL (sdLDL) particles are related to this risk. Objective: To investigate the potential use of sdLDL cholesterol concentration (sdLDL‐C) isolated by an easy precipitation method and to assess the impact of a set of clinical and biochemical variables determined by NMR on sdLDL concentration. Methods: sdLDL‐C and NMR lipid profile were performed in 85 men samples. Association among them was evaluated using Pearson coefficients ( r xy ). A multivariate regression was performed to identify the influence of NMR variables on sdLDL‐C. Results: A strong association between sdLDL‐C and LDLLDL‐P ( r xy = 0.687) and with LDL‐Z ( r xy = −0.603) was found. The multivariate regression explained a 56.8% in sdLDL‐C variation ( P = 8.77.10‐12). BMI, ApoB, triglycerides, FFA, and LDL‐Z showed a significant contribution. The most important ones were ApoB and LDL‐Z; a 1nm increase (LDL‐Z) leads to decrease 126 nmol/L in sdLDL‐C. Conclusion: The association between sdLDL‐C, LDL‐Z, and LDL‐P is clear. From a large number of variables, especially LDL‐Z and apoB influence on sdLDL‐C. Results show that the smaller the LDL size, the higher their cholesterol concentration. Therefore, sdLDL‐C determination by using this easy method would be useful to risk stratification and to uncover cardiovascular residual risk.